Diaphragm and battery
By using polymer binders and non-conductive particles of specific thickness and particle size in lithium-ion battery separators, the problem of shrinkage and air permeability of the separator at high temperatures is solved, and the safety and circulation performance of the battery are improved.
Patent Information
- Application Number
- CN202411370971.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-31
AI Technical Summary
The existing lithium-ion battery separators are prone to shrink or melt at high temperatures, causing contact between positive and negative electrodes, causing short circuits and explosion accidents. The increase in thickness will reduce the heat shrinkage rate but affect battery safety, and the decrease in breathability will affect cycling performance.
The base film having a thickness of 3 to 6 μm and an adhesive layer having a thickness of 0.5 to 1.5 μm is used, and the first polymer binder and non-conductive particles are contained. The peel strength between the adhesive layer and the base film is 10 N/m or more. The ratio of the average particle size of a polymer binder to the thickness of the adhesive layer is (1.3-4): 1, and the average particle size of the second polymer binder is less than 1 μm, ensuring good adhesion between the separator and the electrode sheet and Low heat shrinkage.
The separator is achieved with low thermal shrinkage, high breathability and high bonding strength, which improves the energy density and safety performance of the battery and avoids the battery short circuit and cycle performance degradation.
Smart Images

Figure BDA0005067564980000211 
Figure BDA0005067564980000221 
Figure BDA0005067564980000251
Abstract
Description
Technical Field
[0001] The invention relates to a diaphragm, in particular to a diaphragm and a preparation method thereof and a battery, belonging to the technical field of batteries. Background Art
[0002] Lithium-ion battery is a rechargeable battery with broad application prospects. It has high energy density, long life, small size, no maintenance, and is environmentally friendly. It is favored by various industries and has moved from the fields of mobile phones and laptops to electric bicycles, electric vehicles, energy storage and various portable devices. It is an ideal mobile power source.
[0003] Lithium-ion batteries are usually composed of positive electrodes, negative electrodes, separators, electrolytes, and battery shells. The separator is one of the key internal components, and its function is to separate the positive and negative electrodes of the battery to prevent the positive and negative electrodes from contacting and short-circuiting. At present, the separators used in lithium-ion batteries are generally polyolefin porous membranes. Since the melting point of such polyolefin porous membranes is relatively low, when the battery temperature rises due to internal or external factors, the polyolefin porous membranes will shrink or melt, causing direct contact between the positive and negative electrodes, resulting in a short circuit in the battery, and then causing accidents such as battery combustion and explosion.
[0004] In order to solve these problems, inorganic particles are usually coated on the surface of the diaphragm substrate using a polymer adhesive to form a composite diaphragm, such as ceramic particles coated on the surface of the diaphragm substrate to form a ceramic / polymer composite diaphragm, hoping to use the heat resistance of the ceramic particles to reduce the thermal shrinkage of the diaphragm. At the same time, a layer of polymer adhesive is coated on the surface of the ceramic coating, such as polyvinylidene fluoride (PVDF) to bond the diaphragm to the positive and negative electrodes, which plays a role in fixing the battery structure. Although the method of applying an additional layer of adhesive coating has a better bonding effect, the adhesive is easy to form a film on the surface of the diaphragm, which causes the diaphragm permeability to decrease, further increases the internal resistance of the battery, and leads to the degradation of the battery's cycle performance. In addition, the current lithium-ion battery has higher and higher requirements for energy density, which puts higher and higher requirements on the thickness of the diaphragm. However, reducing the thickness of the diaphragm will cause its thermal shrinkage rate to increase significantly, seriously affecting the safety performance of the battery.
[0005] Based on the above problems, technicians in this field are in urgent need of developing a thin diaphragm with low thermal shrinkage to improve the energy density and safety of the battery. Summary of the invention
[0006] The present invention provides a diaphragm, which has a small thickness, a low heat shrinkage rate, and a high bonding strength with a pole piece, thereby ensuring high energy density and safety of a battery.
[0007] The invention provides a method for preparing a diaphragm, which can produce a diaphragm with small thickness, low heat shrinkage and good adhesion to an electrode sheet, and the preparation method has simple process and is easy to operate.
[0008] The present invention also provides a battery, which comprises the above-mentioned diaphragm and has the properties of high energy density and safety.
[0009] The present invention provides a diaphragm, comprising a base film and an adhesive layer located on at least one side of the base film; the base film has a thickness of 3 to 6 μm, and the adhesive layer has a thickness of 0.5 to 1.5 μm;
[0010] The adhesive layer includes a first polymer binder and non-conductive particles; the ratio of the average particle size D501 of the first polymer binder to the thickness of the adhesive layer is (1.3-4):1; the average particle size D503 of the non-conductive particles is 0.15-0.8 μm; the peel strength between the adhesive layer and the base film is above 10 N / m.
[0011] The separator as described above, wherein the average particle size D501 of the first polymer binder is 1 to 6 μm;
[0012] And / or, the glass transition temperature Tg1 of the first polymer binder is 45-95°C.
[0013] The diaphragm as described above, wherein the mass percentage of the first polymer binder in the adhesive layer is 3% to 15%;
[0014] And / or, the first polymer binder is obtained by polymerizing a monomer containing an unsaturated bond, wherein:
[0015] The monomer containing an unsaturated bond includes one or more of a vinyl monomer, a (meth)acrylate monomer, a maleate monomer, an itaconate monomer, a maleimide monomer, and a (meth)acrylamide monomer;
[0016] And / or, the monomer containing an unsaturated bond includes one or more of a monomer having a carboxyl group, a monomer having a sulfonic acid group, a monomer having a phosphoric acid group, a monomer having a hydroxyl group, a monomer having an amino group, a monomer having an epoxy group, and a monomer having a cyano group.
[0017] In the separator as described above, the ratio of the average particle size D503 of the non-conductive particles to the average particle size D501 of the first polymer binder is 1:2.3-20.
[0018] In the separator as described above, the average particle size D103 of the non-conductive particles is 0.05 to 0.6 μm, and the average particle size D903 of the non-conductive particles is 0.5 to 2 μm.
[0019] The separator as described above, wherein the mass percentage of the non-conductive particles in the bonding layer is 70% to 93.4%;
[0020] And / or, the non-conductive particles include one or more of alumina, aluminum oxide, boehmite, silicon dioxide, titanium dioxide, zirconium dioxide, calcium oxide, magnesium oxide, magnesium hydroxide, calcium carbonate, barium titanate, barium sulfate, organic polymer microspheres, and organic polymer fibers. When the non-conductive particles are organic polymer fibers, the average particle size specifically refers to the diameter of the polymer fibers.
[0021] In the above-mentioned separator, the adhesive layer further comprises a second polymer binder, and the average particle size D502 of the second polymer binder is 0.05-1 μm.
[0022] Preferably, the diameter distance of the second polymer binder is less than 1.
[0023] Preferably, the Tg2 of the second polymer binder is below 20°C.
[0024] Preferably, the second polymer binder includes at least one of polyacrylates and styrene-butadiene latex;
[0025] Preferably, the mass percentage of the second polymer binder in the adhesive layer is 3% to 10%.
[0026] The diaphragm as described above, wherein the adhesive layer further includes a rheology regulator and / or an auxiliary agent, and the auxiliary agent includes a wetting agent and / or a defoaming agent; wherein the rheology regulator includes one or more of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, and polyacrylate; and / or the mass percentage of the rheology regulator in the adhesive layer is 0.5% to 3%; and / or the mass percentage of the auxiliary agent in the adhesive layer is 0.1% to 2%; and / or the base film includes a polyolefin film and / or a non-woven fabric film, and the polyolefin film includes a polyethylene base film and / or a polypropylene base film.
[0027] The diaphragm as described above, wherein the thermal shrinkage of the diaphragm after baking at 130°C±5°C for 60min±5min is less than 5%;
[0028] And / or, the permeability increment of the diaphragm is not higher than 50s / 100cc.
[0029] The present invention also provides a diaphragm, comprising a base film and an adhesive layer located on at least one side of the base film; the base film has a thickness of 3 to 6 μm, and the adhesive layer has a thickness of 0.5 to 1.5 μm;
[0030] The bonding layer includes a first polymer binder, non-conductive particles and a second polymer binder; the ratio of the average particle size D501 of the first polymer binder to the thickness of the bonding layer is (1.3-4):1; the average particle size D503 of the non-conductive particles is 0.15-0.8 μm; the average particle size D502 of the second polymer binder is 0.05-1 μm, and the diameter distance of the second polymer binder is less than 1.
[0031] Preferably, the ratio of the average particle size D501 of the first polymer binder to the thickness of the adhesive layer is (1.3-4):1.
[0032] Preferably, the average particle size D501 of the first polymer binder is 1 to 6 μm;
[0033] And / or, the glass transition temperature Tg1 of the first polymer binder is 45-95°C.
[0034] Preferably, the mass percentage of the first polymer binder in the adhesive layer is 3% to 15%;
[0035] And / or, the first polymer binder is obtained by polymerizing a monomer containing an unsaturated bond, wherein:
[0036] The monomer containing an unsaturated bond includes one or more of a vinyl monomer, a (meth)acrylate monomer, a maleate monomer, an itaconate monomer, a maleimide monomer, and a (meth)acrylamide monomer;
[0037] And / or, the monomer containing an unsaturated bond includes one or more of a monomer having a carboxyl group, a monomer having a sulfonic acid group, a monomer having a phosphoric acid group, a monomer having a hydroxyl group, a monomer having an amino group, a monomer having an epoxy group, and a monomer having a cyano group.
[0038] Preferably, the ratio of the average particle size D503 of the non-conductive particles to the average particle size D501 of the first polymer binder is 1:(2.3-20).
[0039] Preferably, the average particle size D103 of the non-conductive particles is 0.05 to 0.6 μm, and the average particle size D903 of the non-conductive particles is 0.5 to 2 μm;
[0040] And / or, the mass percentage of the non-conductive particles in the adhesive layer is 70% to 93.4%;
[0041] And / or, the non-conductive particles include one or more of alumina, aluminum oxide, boehmite, silicon dioxide, titanium dioxide, zirconium dioxide, calcium oxide, magnesium oxide, magnesium hydroxide, calcium carbonate, barium titanate, barium sulfate, organic polymer microspheres, and organic polymer fibers.
[0042] Preferably, the Tg2 of the second polymer binder is below 20°C;
[0043] And / or, the second polymer binder includes at least one of polyacrylates and styrene-butadiene latex;
[0044] And / or, the mass percentage of the second polymer binder in the adhesive layer is 3% to 10%.
[0045] The diaphragm as described above, wherein the adhesive layer further includes a rheology regulator and / or an auxiliary agent, and the auxiliary agent includes a wetting agent and / or a defoaming agent; wherein the rheology regulator includes one or more of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, and polyacrylate; and / or the mass percentage of the rheology regulator in the adhesive layer is 0.5% to 3%; and / or the mass percentage of the auxiliary agent in the adhesive layer is 0.1% to 2%; and / or the base film includes a polyolefin film and / or a non-woven fabric film, and the polyolefin film includes a polyethylene base film and / or a polypropylene base film.
[0046] The diaphragm as described above, wherein the thermal shrinkage of the diaphragm after baking at 130°C±5°C for 60min±5min is less than 5%;
[0047] And / or, the permeability increment of the diaphragm is not higher than 50s / 100cc.
[0048] The present invention provides a battery, comprising a positive electrode sheet, a negative electrode sheet, and the above-mentioned separator, wherein the separator is located between the positive electrode sheet and the negative electrode sheet.
[0049] The battery as described above, wherein
[0050] The bonding force between the separator and the positive electrode sheet is not less than 1.5 N / m;
[0051] and / or, the bonding force between the separator and the negative electrode sheet is not less than 0.5 N / m;
[0052] And / or, the battery is a lithium-ion battery.
[0053] The diaphragm, the preparation method of the diaphragm and the battery provided by the present invention have a base film and an adhesive layer in the diaphragm that are significantly thinner than the thickness of the corresponding parts of the existing diaphragm. In order to overcome the problems caused by the reduction of the thickness of the base film and the adhesive layer, specifically for the base film with a thickness of 3 to 6 μm and the adhesive layer with a thickness of 0.5 to 1.5 μm, the present invention adopts a first polymer binder with an average particle size D501 greater than the thickness of the adhesive layer, and the ratio of the average particle size D501 of the first polymer binder to the thickness of the adhesive layer is (1.3 to 4):1; the average particle size D503 of the non-conductive particles is 0.15 to 0.8 μm; and the peel strength between the adhesive layer and the base film is controlled to be above 10 N / m. In the case of the base film and the adhesive layer with the above-mentioned thickness, the diaphragm can be effectively bonded to the positive and negative electrode sheets, and the problem of increased thermal shrinkage of the diaphragm caused by the reduction of the thickness of the base film and the adhesive layer can be effectively suppressed, thereby ensuring the high energy density and safety of the battery. DETAILED DESCRIPTION
[0054] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0055] The present invention provides a diaphragm, which includes a base film and an adhesive layer located on at least one side of the base film; the thickness of the base film is 3 to 6 μm, and the thickness of the adhesive layer is 0.5 to 1.5 μm; the adhesive layer includes a first polymer binder and non-conductive particles; the ratio of the average particle size D501 of the first polymer binder to the thickness of the adhesive layer is (1.3 to 4):1; the average particle size D503 of the non-conductive particles is 0.15 to 0.8 μm; and the peel strength between the adhesive layer and the base film is above 10 N / m.
[0056] The separator of the present invention is composed of a base film and an adhesive layer, and the adhesive layer is located on the surface of at least one side of the base film, that is, the adhesive layer can be bonded to a single side of the base film or to both sides of the base film.
[0057] The thickness of the base film in the embodiment of the present invention is 3-6 μm, for example, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm or 6 μm.
[0058] The thickness of the adhesive layer in the embodiment of the present invention is 0.5-1.5 μm, for example, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm or 1.5 μm.
[0059] The components in the adhesive layer of the embodiment of the present invention include a first polymer adhesive, the average particle size D501 of the first polymer adhesive is greater than the thickness of the adhesive layer, and the average particle size D50 refers to the volume distribution average particle size Dv50, that is, the particle size corresponding to when the cumulative particle size distribution percentage reaches 50%.
[0060] Specifically, the average particle size D501 of the first polymer binder in the embodiment of the present invention can be obtained by measuring the first polymer binder using a laser particle size analyzer or other equipment. After the diaphragm is prepared, the first polymer binder in the adhesive layer of the diaphragm can be tested by the following steps: the diaphragm is tested using a SEM to test the average particle size of at least 20 particles, and then the average value is taken as the final measurement result.
[0061] According to the present invention, the ratio of the average particle size D501 of the first polymer binder to the thickness of the adhesive layer is (1.3-4):1. When the ratio of the average particle size D501 of the first polymer binder to the thickness of the adhesive layer is within the above range, it is beneficial to improve the bonding strength between the diaphragm and the electrode sheet, inhibit the thermal shrinkage of the diaphragm, and ensure the air permeability of the diaphragm. If the ratio is too large, when the thickness of the adhesive layer is thin (0.5-1.5 μm), there may be a problem of the first polymer binder falling off due to the excessive average particle size D501 of the first polymer binder, which in turn causes the bonding strength between the diaphragm and the electrode sheet to decrease, and the inhibitory effect on the thermal shrinkage of the diaphragm will also decrease. If the ratio is too small, it is not conducive to improving the bonding strength between the diaphragm and the electrode sheet, and the air permeability of the diaphragm will also decrease to a certain extent.
[0062] Preferably, the average particle size D501 of the first polymer binder is 1 to 6 μm. Specifically, for example, the average particle size D501 of the first polymer binder can be 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm or 6 μm.
[0063] In the present invention, preferably, the glass transition temperature Tg1 of the first polymer binder is 45 to 95°C, for example, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or 95°C.
[0064] The glass transition temperature refers to the transition temperature from the glass state to the highly elastic state inside the material. When the glass transition temperature of the polymer particles is within the above range, it is very beneficial to improve the bonding strength between the diaphragm and the pole piece, and can further improve the heat resistance of the diaphragm, and can also match the processing temperature of the diaphragm to reduce the processing difficulty.
[0065] The method for measuring the glass transition temperature of the polymer particles in the above binder is well known to those skilled in the art, for example, by using a conventional differential scanning calorimeter for detection.
[0066] The glass transition temperature Tg1 of the first polymer binder is within the above range, which can effectively improve the heat resistance of the diaphragm while ensuring the adhesion of the first polymer binder, thereby further reducing the thermal shrinkage rate of the diaphragm, thereby avoiding the diaphragm shrinking or melting when the battery temperature rises, causing a battery short circuit, and improving the safety of the battery.
[0067] The present invention adopts the above scheme, when the thickness of the base film and the adhesive layer in the diaphragm is small, the thermal shrinkage rate of the diaphragm is low, the air permeability is high, and the diaphragm has good adhesion with the electrode sheet. The diaphragm is applied to the battery, which can improve the energy density, cycle performance and safety of the battery. The inventor believes that the reason may be that the average particle size of the first polymer binder is appropriate, and it can be evenly dispersed in the adhesive layer, so as to avoid the first polymer binder from falling off from the adhesive layer, ensure the structure of the diaphragm, and improve the safety of the battery. Moreover, the first polymer binder is dispersed and embedded in the adhesive layer, and the hot pressing will not form a film, especially the ratio of the average particle size D501 of the first polymer binder to the thickness of the adhesive layer is (1.3-4): 1, which can effectively avoid the decrease of the air permeability of the diaphragm, and then ensure the migration rate of ions in the battery and improve the cycle performance of the battery. Controlling the peel strength between the adhesive layer and the base film to be above 10N / m can effectively ensure the close bonding between the adhesive layer and the base film, and can also effectively inhibit the thermal shrinkage of the diaphragm. In addition, the low thickness of the base film and the separator can avoid the increase of the internal resistance of the battery and shorten the length of the migration path of ions between the positive and negative electrodes, thereby improving the energy density of the battery.
[0068] In a specific embodiment, the mass percentage of the first polymer binder in the adhesive layer is 3% to 15%, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%. When the mass percentage of the first polymer binder in the adhesive layer is within the above range, the first polymer binder can make the diaphragm have high adhesion, low thermal shrinkage and high air permeability, and can avoid the decrease in the air permeability of the diaphragm caused by too high a content of the first polymer binder, or the insufficient adhesion of the diaphragm caused by too low a content of the first polymer binder, thereby improving the cycle performance and safety of the battery to a greater extent.
[0069] In the present invention, the mass percentage of the first polymer binder in the above-mentioned adhesive layer can be based on the mass percentage of the first polymer binder in the slurry when preparing the adhesive layer.
[0070] In a specific embodiment, the first polymer binder is obtained by polymerizing a monomer containing an unsaturated bond.
[0071] Specifically, the monomer containing an unsaturated bond may include one or more of a vinyl monomer, a (meth)acrylate monomer, a maleate monomer, an itaconate monomer, a maleimide monomer, and a (meth)acrylamide monomer;
[0072] In addition, the monomer containing an unsaturated bond may include one or more of a monomer having a carboxyl group, a monomer having a sulfonic acid group, a monomer having a phosphoric acid group, a monomer having a hydroxyl group, a monomer having an amino group, a monomer having an epoxy group, and a monomer having a cyano group.
[0073] The vinyl monomers of the embodiments of the present invention include, but are not limited to, aliphatic vinyl hydrocarbon compounds, alicyclic vinyl hydrocarbon compounds, aromatic vinyl hydrocarbon compounds, allyl compounds, and vinyl compounds containing heteroatoms (illustratively including, but not limited to, vinyl esters, vinyl (thio) ethers, vinyl ketones, and vinyl sulfones);
[0074] Wherein, the aliphatic vinyl hydrocarbon compounds include, but are not limited to, olefins having 2 to 12 carbon atoms (illustratively including, but not limited to, ethylene, propylene, butene, isobutylene, pentene, heptene, diisobutylene, octene, dodecene, octadecene), α-olefins having 3 to 24 carbon atoms, and dienes having 4 to 12 carbon atoms (illustratively including, but not limited to, butadiene, isoprene, 1,4-pentadiene, 1,6-hexadiene, and 1,7-octadiene);
[0075] Alicyclic vinyl hydrocarbon compounds include, but are not limited to, monocyclic or bicyclic olefins having 6 to 15 carbon atoms (exemplarily including, but not limited to, cyclohexene, vinylcyclohexene, and ethylidene bicycloheptene), monocyclic or bicyclic dienes having 5 to 12 carbon atoms (exemplarily including, but not limited to, cyclopentadiene, cycloheptadiene, dicyclopentadiene, and dicycloheptadiene), and terpene compounds (exemplarily including, but not limited to, limonene and indene);
[0076] Aromatic vinyl hydrocarbon compounds include, but are not limited to, styrene and substituted styrenes. Exemplary substituted styrenes include, but are not limited to, α-methylstyrene, vinyltoluene, 2,4-dimethylstyrene, ethylstyrene, isopropylstyrene, butylstyrene, phenylstyrene, cyclohexylstyrene, benzylstyrene, crotonylstyrene, divinylbenzene, divinyltoluene, divinylxylene, trivinylbenzene, vinylnaphthalene, and p-tert-butylstyrene.
[0077] The (meth)acrylate monomers of the embodiments of the present invention include methacrylates and acrylates, including but not limited to: methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-pentyl acrylate, isopentyl acrylate, n-hexyl acrylate, n-octyl acrylate, isooctyl acrylate, isobornyl acrylate, phenoxyethyl acrylate, dicyclopentenyl acrylate, cyclohexyl acrylate, benzyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, methyl methacrylate, n-pentyl methacrylate, isoamyl methacrylate, n-hexyl methacrylate, isooctyl methacrylate, isobornyl methacrylate, phenoxyethyl methacrylate, dicyclopentenyl methacrylate, cyclohexyl methacrylate, benzyl methacrylate, ethylene glycol diacrylate, ethylene glycol dimethacrylate, ethoxylated ethylene glycol diacrylate, ethoxylated ethylene glycol dimethacrylate, allyl methacrylate, diallyl phthalate, diallyl adipate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol diacrylate, pentaerythritol dimethacrylate, pentaerythritol triacrylate, pentaerythritol trimethacrylate.
[0078] The maleate monomers of the embodiments of the present invention illustratively include, but are not limited to, C1-C12 monoalkyl maleate and C1-C12 dialkyl maleate.
[0079] The itaconate ester monomers of the embodiments of the present invention illustratively include, but are not limited to: itaconate C1-C12 monoesters and itaconate C1-C12 diesters.
[0080] The maleimide monomers of the embodiments of the present invention illustratively include, but are not limited to: maleimide, C1-C12 alkyl-substituted maleimide, and C6-C16 aryl-substituted maleimide.
[0081] The (meth)acrylamide monomers of the embodiments of the present invention illustratively include but are not limited to (meth)acrylamide, N-methyl (meth)acrylamide, N-butylacrylamide, acetylacetonate acrylamide, N-hydroxymethyl (meth)acrylamide, N,N'-methylenebis [(meth)acrylamide], cinnamamide, N,N-dimethylacrylamide, N,N-dibenzylacrylamide, methacrylamide, N-methyl N-vinylacetamide and N-vinylpyrrolidone, C1~C12 alkyl substituted acrylamide, C6~C18 aromatic substituted acrylamide, etc.
[0082] The monomers having a carboxyl group in the embodiments of the present invention include, but are not limited to, unsaturated monocarboxylic acids having 3 to 30 carbon atoms (exemplarily including, but not limited to, (meth)acrylic acid (including acrylic acid and / or methacrylic acid, the same below), crotonic acid, isocrotonic acid and cinnamic acid, etc.), unsaturated dicarboxylic acids (anhydrides) having 3 to 30 carbon atoms (exemplarily including, but not limited to, maleic acid (anhydride), fumaric acid, itaconic acid, citraconic acid (anhydride) and mesaconic acid, etc.), monoalkyl (1 to 24 carbon atoms) esters of unsaturated dicarboxylic acids having 3 to 30 carbon atoms (exemplarily including, but not limited to, monomethyl maleate, monooctadecyl maleate, monoethyl fumarate, monobutyl itaconate, ethylene glycol monoether and monoeicosyl citrate, etc.), etc.; the vinyl monomers having a carboxyl group may also be in the form of a salt, such as an alkali metal salt (lithium salt, sodium salt and potassium salt, etc.), an amine salt or a quaternary ammonium salt.
[0083] The monomers having sulfonic acid groups in the embodiments of the present invention include, but are not limited to, olefin sulfonic acids having 2 to 14 carbon atoms (exemplarily including, but not limited to, vinyl sulfonic acid, (methyl) allyl sulfonic acid, and methyl vinyl sulfonic acid, etc.), styrene sulfonic acid and its alkyl (2 to 24 carbon atoms) derivatives (exemplarily including, but not limited to, α-methylstyrene sulfonic acid, etc.), (meth) acrylate sulfo (hydroxy) alkyl esters having 5 to 18 carbon atoms (exemplarily including, but not limited to (meth) acrylate sulfo (hydroxy) alkyl esters having 5 to 18 carbon atoms, Acid, etc.), sulfo(hydroxy)alkyl(meth)acrylamide having 5-18 carbon atoms (exemplarily including but not limited to 2-(meth)acryloylamino-2,2-dimethylethanesulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, 3-(meth)acrylamide-2-hydroxypropanesulfonic acid), alkyl (3-18 carbon atoms) allyl sulfosuccinic acid (exemplarily including but not limited to propyl allyl sulfosuccinic acid, butyl allyl sulfosuccinic acid, 2-ethylhexyl-allyl sulfosuccinic acid); the vinyl monomer having a sulfonic acid group can also be in the form of a salt, such as an alkali metal salt (lithium salt, sodium salt and potassium salt, etc.), an amine salt or a quaternary ammonium salt.
[0084] The monomers having a phosphate group in the embodiments of the present invention include, but are not limited to, (meth)acryloyloxyalkyl phosphate monoesters (alkyl groups having 1-24 carbon atoms) (exemplarily including, but not limited to, 2-hydroxyethyl (meth)acryloyl phosphate and phenyl-2-acryloyloxyethyl phosphate, etc.), (meth)acryloyloxyalkyl phosphate (alkyl groups having 1-24 carbon atoms, exemplarily including, but not limited to, 2-acryloyloxyethyl phosphate); the vinyl monomers having a phosphate group may also be in the form of a salt, such as an alkali metal salt (lithium salt, sodium salt, potassium salt, etc.), an amine salt, or a quaternary ammonium salt.
[0085] The monomers having hydroxyl groups in the embodiments of the present invention include, but are not limited to, vinyl monomers having hydroxyl groups: hydroxystyrene, N-hydroxymethyl (meth) acrylamide, hydroxyethyl (meth) acrylate, hydroxypropyl (meth) acrylate, hydroxybutyl (meth) acrylate, polyethylene glycol mono[(meth) acrylate] ester, (meth) allyl alcohol, crotyl alcohol, isocrotyl alcohol, 1-butene-3-ol, 2-butene-1-ol, 2-butene-1,4-diol, propargyl alcohol, 2-hydroxyethyl propenyl ether, and sucrose allyl ether, etc.
[0086] Monomers having amino groups according to embodiments of the present invention include, but are not limited to, aminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, tert-butylaminoethyl methacrylate, N-aminoethyl (meth)acrylamide, (meth)allylamine, morpholinoethyl (meth)acrylate, 4-vinylpyridine, 2-vinylpyridine, crotylamine, N,N-dimethylaminostyrene, α-acetamidomethyl acrylate, vinylimidazole, N-vinylpyrrole, N-vinylthiopyrrolidone, N-arylphenylenediamine, aminocarbazole, aminothiazole, aminoindole, aminopyrrole, aminoimidazole, aminothiothiazole and monomer salts thereof.
[0087] The monomers having epoxy groups in the embodiments of the present invention include, but are not limited to, vinyl monomers having epoxy groups and having 6 to 18 carbon atoms: glycidyl (meth)acrylate, tetrahydrofuran (meth)acrylate, and allyl glycidyl ester.
[0088] The monomers having a cyano group in the embodiment of the present invention include, but are not limited to, vinyl monomers having a cyano group and having 3 to 10 carbon atoms: (meth)acrylonitrile, cyanostyrene, and cyanoacrylate.
[0089] In a specific embodiment, the second polymer binder is at least one of polyacrylates and styrene-butadiene latexes, wherein polyacrylates are obtained by polymerizing at least one acrylate or methacrylate monomer, and styrene-butadiene latexes are obtained by copolymerizing at least butadiene and styrene. When preparing the second polymer binder, the monomer used to prepare the first polymer binder can also be copolymerized.
[0090] According to the present invention, the average particle size D503 of the non-conductive particles in the adhesive layer is less than the thickness of the adhesive layer. Specifically, the average particle size D503 of the non-conductive particles in the adhesive layer is 0.15 to 0.8 μm. For example, it can be 0.15 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm or 0.8 μm, etc. More preferably, the average particle size D103 of the non-conductive particles is 0.05 to 0.6 μm, and the average particle size D903 of the non-conductive particles is 0.5 to 2 μm. When the thickness of the base film of the diaphragm is 3 to 6 μm and the thickness of the adhesive layer is 0.5 to 1.5 μm, if the average particle size D503 of the non-conductive particles exceeds 0.8 μm, the thermal shrinkage rate of the diaphragm will increase significantly.
[0091] Preferably, the ratio of the average particle size D503 of the non-conductive particles to the average particle size D501 of the first polymer binder is 1:(2.3-20). When the thickness of the base film of the separator is 3-6 μm and the thickness of the adhesive layer is 0.5-1.5 μm, when the ratio of the average particle size D503 of the non-conductive particles to the average particle size D501 of the first polymer binder is 1:(2.3-20), the thermal shrinkage of the separator can be better suppressed and good air permeability can be maintained.
[0092] Specifically, the average particle size of the non-conductive particles of the embodiment of the present invention can be obtained directly from the supplier when purchasing. The average particle size of the non-conductive particles coated on the base film can be obtained by testing in the following steps: using a scanning electron microscope (SEM) to test the separator, testing the average particle size of at least 20 particles, and then taking the average value as the final measurement result.
[0093] The mass percentage of the non-conductive particles in the above-mentioned adhesive layer is 70% to 93.4%. For example, it can be 70%, 75%, 80%, 85%, 90% or 93.4%. When the mass percentage of the non-conductive particles in the adhesive layer is within the above-mentioned range, the mechanical strength and thermal stability of the diaphragm can be effectively improved, so that the thermal shrinkage rate of the diaphragm is lower, thereby making the battery safer.
[0094] In the present invention, in a specific embodiment, the non-conductive particles may include inorganic ceramic particles and / or organic polymer particles, and may specifically include one or more of aluminum oxide, aluminum oxide, boehmite, silicon dioxide, titanium dioxide, zirconium dioxide, calcium oxide, magnesium oxide, magnesium hydroxide, calcium carbonate, barium titanate, barium sulfate, organic polymer microspheres, and organic polymer fibers. The aluminum oxide of the embodiment of the present invention includes hydrated aluminum oxide. When the non-conductive particles are selected from the above materials, the non-conductive particles can better improve the mechanical strength and thermal stability of the diaphragm, further reduce the thermal shrinkage of the diaphragm, and further improve the safety of the battery. The above-mentioned non-conductive particles can be obtained commercially. As known to those skilled in the art, the D503, D103 and D903 values of the non-conductive particles can be obtained from the supplier when purchasing. In the present invention, non-conductive particles with suitable parameters are selected for use.
[0095] As mentioned above, in the present invention, the peel strength between the adhesive layer and the base film is 10N / m or more. In order to achieve effective bonding between the adhesive layer and the base film, the adhesive layer further includes a second polymer binder. In the present invention, by adjusting the second polymer binder in the adhesive layer or its construction process, the peel strength between the final adhesive layer and the base film is 10N / m or more.
[0096] In the present invention, the second polymer binder may be a commonly used binder for bonding non-conductive particles on the surface of the separator, for example, at least one of a polyacrylate binder and a styrene-butadiene latex binder may be used.
[0097] In the present invention, the average particle size D502 of the second polymer binder is 0.05 to 1 μm.
[0098] According to the present invention, the diameter pitch of the second polymer binder is less than 1, preferably less than 0.8, specifically less than 0.6, less than 0.5, etc. This is beneficial for further suppressing the thermal shrinkage of the separator.
[0099] As is well known in the prior art, the span is expressed as SPAN=(D90-D10) / D50.
[0100] In the present invention, by controlling the peel strength between the adhesive layer and the base film to be above 10 N / m, the separator can be ensured to have a low thermal shrinkage rate when the thickness of the base film is 3 to 6 μm and the thickness of the adhesive layer is 0.5 to 1.5 μm.
[0101] According to the present invention, the peel strength between the adhesive layer and the base film can be tested by a method known in the prior art, for example, by the test method described in the performance test section of the present invention.
[0102] In a specific embodiment, the adhesive layer further includes a second polymer binder, and the second polymer binder includes at least one of polyacrylates and styrene-butadiene latex. When the adhesive layer further includes the second polymer binder, the second polymer binder can bond the non-conductive particles in the adhesive layer to the first polymer binder and other components, thereby preventing the components in the adhesive layer from falling off and improving the stability of the adhesive layer. In addition, the second polymer binder can enhance the bonding force between the adhesive layer and the substrate, thereby stabilizing the structure of the separator and preventing the positive and negative electrodes of the battery from being displaced due to the adhesive layer falling off the substrate surface, thereby improving the safety of the battery.
[0103] Preferably, the mass percentage of the second polymer binder in the adhesive layer is 3% to 10%, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10, etc. When the mass percentage of the second polymer binder in the adhesive layer is within the above range, the adhesive layer can be firmly attached to the surface of the substrate, thereby further improving the safety of the battery, and can avoid the decrease in the air permeability of the separator due to excessive second polymer binder, thereby further improving the cycle performance of the battery.
[0104] Preferably, the Tg2 of the second polymer binder is 20°C or less.
[0105] The second polymer binder meeting the requirements of the present invention can be prepared by self-production or commercial purchase, and has an average particle size in the range of 0.05 to 1 μm, a diameter distance in the range of 0.4 to 0.9, and a glass transition temperature in the range of -50 to 20°C.
[0106] The second polymer binder of the present invention can be prepared by emulsion polymerization, and the specific preparation method is as follows:
[0107] Weigh 0.1-3 parts of surfactant and 300-400 parts of deionized water into a stirring container, add 100-200 parts of monomer, control the stirring speed to 200±50rpm, stir and heat to 74±1°C, then add 0.2-2 parts of initiator, maintain stirring reaction at 469-79°C for 3-6h, then raise the temperature to 74-84°C, continue the reaction for 3-5h, and obtain a second polymer binder emulsion with a solid content of 20-40%.
[0108] A person skilled in the art may select corresponding monomers based on the above preparation method and fine-tune the process conditions according to the type of binder to be prepared, such as a styrene-butadiene latex second polymer binder or a polyacrylate second polymer binder.
[0109] The monomers for preparing the styrene-butadiene latex include at least one aromatic vinyl monomer selected from styrene units, α-methylstyrene units, vinyltoluene units, 2-vinylnaphthalene units, methylvinylnaphthalene units, vinylanthracene units, and methylvinylanthracene units, and at least one conjugated diene monomer selected from 1,3-butadiene, 1,3-pentadiene, 2-methyl-1,3-butadiene, 1,3-cyclopentadiene, and 1,3-hexadiene. Other modified monomers may also be added as needed. During preparation, those skilled in the art may select and adjust the addition amount of each monomer as needed.
[0110] The monomers for preparing polyacrylates include at least one of methyl (meth)acrylate, ethyl (meth)acrylate, isobutyl acrylate, butyl (meth)acrylate, 2-isooctyl (meth)acrylate, lauryl (meth)acrylate, octadecyl (meth)acrylate, behenyl (meth)acrylate, caprolactone acrylate, benzyl acrylate, and ethylene glycol diacrylate. Other monomers, such as divinylbenzene, etc., may also be added as needed. During preparation, those skilled in the art may select and adjust the amount of each monomer added as needed.
[0111] The surfactant can be an emulsifier commonly used in emulsion polymerization, such as at least one of sodium lauryl alcohol, potassium lauryl alcohol, sodium dodecyl sulfate, ammonium dodecyl sulfate, sodium dodecyl polyoxyethylene ether sulfate, ammonium dodecyl polyoxyethylene ether sulfate, sodium dodecylbenzene sulfonate, fatty alcohol polyoxyethylene ether, and alkylphenol polyoxyethylene ether.
[0112] The initiator may be a common initiator for emulsion polymerization, such as at least one of persulfates, a combination of persulfate-bisulfite, and a combination of peroxide-bisulfite.
[0113] As another embodiment of the present invention, the diaphragm includes a base film and an adhesive layer located on at least one side of the base film; the base film has a thickness of 3 to 6 μm, and the adhesive layer has a thickness of 0.5 to 1.5 μm;
[0114] The bonding layer includes a first polymer binder, non-conductive particles and a second polymer binder; the ratio of the average particle size D501 of the first polymer binder to the thickness of the bonding layer is (1.3-4):1; the average particle size D503 of the non-conductive particles is 0.15-0.8 μm; the average particle size D502 of the second polymer binder is 0.05-1 μm, and the diameter distance of the second polymer binder is less than 1.
[0115] In the present invention, when the thickness of the base film is 3 to 6 μm, the thickness of the adhesive layer is 0.5 to 1.5 μm, and the average particle size D501 of the first polymer binder is greater than the thickness of the adhesive layer, the average particle size D502 of the second polymer binder is controlled to be 0.05 to 1 μm, and the diameter pitch of the second polymer binder is less than 1, excellent heat resistance and low thermal shrinkage can be achieved when the overall thickness of the diaphragm is relatively thin.
[0116] As mentioned above, the ratio of the average particle size D501 of the first polymer binder to the thickness of the adhesive layer is (1.3-4):1. When the ratio of the average particle size D501 of the first polymer binder to the thickness of the adhesive layer is within the above range, it is beneficial to improve the bonding strength between the diaphragm and the electrode sheet, inhibit the thermal shrinkage of the diaphragm, and ensure the air permeability of the diaphragm. If the ratio is too large, when the thickness of the adhesive layer is thin (0.5-1.5 μm), there may be a problem of the first polymer binder falling off due to the excessive average particle size D501 of the first polymer binder, which in turn causes the bonding strength between the diaphragm and the electrode sheet to decrease, and the effect of inhibiting the thermal shrinkage of the diaphragm will also decrease. If the ratio is too small, it is not conducive to improving the bonding strength between the diaphragm and the electrode sheet, and the air permeability of the diaphragm will also decrease to a certain extent.
[0117] Preferably, the average particle size D501 of the first polymer binder is 1 to 6 μm. Specifically, for example, the average particle size D501 of the first polymer binder can be 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm or 6 μm.
[0118] In the present invention, preferably, the glass transition temperature Tg1 of the first polymer binder is 45 to 95°C, for example, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or 95°C.
[0119] The present invention adopts the above scheme, and when the thickness of the base film and the adhesive layer in the diaphragm is small, the diaphragm has a low thermal shrinkage rate, high air permeability, and good adhesion with the electrode sheet. The diaphragm is applied to the battery, which can improve the energy density, cycle performance and safety of the battery. The inventor believes that the reason may be that the average particle size of the first polymer binder is appropriate, and it can be evenly dispersed in the adhesive layer, so as to avoid the first polymer binder from falling off from the adhesive layer, ensure the structure of the diaphragm, and improve the safety of the battery. In addition, the first polymer binder is dispersed and embedded in the adhesive layer, and hot pressing will not form a film. In particular, the ratio of the average particle size D501 of the first polymer binder to the thickness of the adhesive layer is (1.3-4):1, which can effectively avoid the decrease in the air permeability of the diaphragm, thereby ensuring the migration rate of ions in the battery and improving the cycle performance of the battery. The average particle size D502 of the second polymer binder is controlled to be 0.05-1 μm, and the diameter pitch of the second polymer binder is less than 1. Through the joint action of the first polymer binder, the second polymer binder and the non-conductive particles, the close bonding between the adhesive layer and the base film can be effectively ensured, and the thermal shrinkage of the diaphragm can also be effectively suppressed.
[0120] In this embodiment, the content of the first polymer binder in the adhesive layer and the specific materials that can be used are as described above and will not be repeated here.
[0121] According to the present invention, the average particle size D503 of the non-conductive particles in the adhesive layer is less than the thickness of the adhesive layer. Preferably, the ratio of the average particle size D503 of the non-conductive particles to the average particle size D501 of the first polymer binder is 1:(2.3-20). The average particle size D503 of the non-conductive particles is 0.15-0.8 μm. If the average particle size D503 of the non-conductive particles exceeds 0.8 μm, the thermal shrinkage rate of the diaphragm will increase significantly.
[0122] Preferably, the average particle size D103 of the non-conductive particles is 0.05-0.6 μm, and the average particle size D903 of the non-conductive particles is 0.5-2 μm. At this time, the non-conductive particles can better cooperate with the second polymer binder with the aforementioned average particle size and diameter distance, so that the diaphragm has excellent heat resistance and low thermal shrinkage at a lower thickness.
[0123] When the thickness of the base film of the diaphragm is 3 to 6 μm, the thickness of the adhesive layer is 0.5 to 1.5 μm, the average particle size D502 of the second polymer binder is 0.05 to 1 μm, and the diameter distance is less than 1, and the ratio of the average particle size D503 of the non-conductive particles to the average particle size D501 of the first polymer binder is 1:(2.3 to 20), the first polymer binder, the non-conductive particles and the second polymer binder cooperate to better suppress the thermal shrinkage of the diaphragm and maintain good air permeability.
[0124] In this embodiment, the content of the non-conductive particles and the specific materials that can be used are as described above and will not be repeated here.
[0125] Preferably, the Tg2 of the second polymer binder is 20°C or less.
[0126] The content of the second polymer binder and the specific materials that can be used are as described above and will not be repeated here.
[0127] In the embodiment of the present invention, the first polymer binder can be used as the main bonding component for bonding the diaphragm and the electrode sheet, that is, the diaphragm is mainly bonded to the electrode sheet through the first polymer binder in the bonding layer. The second polymer binder can be mainly used to bond the non-conductive particles in the bonding layer and the first polymer binder (particles) and other components to improve the stability of the bonding layer, and can also be used together with the first polymer binder as a bonding material for bonding the diaphragm and the electrode sheet to improve the bonding force between the diaphragm and the electrode sheet.
[0128] In a specific embodiment, the adhesive layer also includes a rheology regulator and / or an auxiliary agent, and the auxiliary agent includes a wetting agent and / or a defoaming agent; wherein the rheology regulator includes one or more of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, and polyacrylate. The rheology regulator of the embodiment of the present invention can adjust the viscosity of the adhesive layer slurry, which is convenient for coating the adhesive layer slurry on the base film, thereby obtaining a diaphragm with high stability. The function of the wetting agent of the embodiment of the present invention is to make it easier for the adhesive layer slurry to be evenly spread on the base film, making the adhesive layer more uniform, so as to better control the thickness of the adhesive layer. The defoaming agent of the embodiment of the present invention can eliminate bubbles generated in the adhesive layer slurry and during the coating process, prevent defects in the diaphragm, and facilitate the subsequent application of the diaphragm.
[0129] In a specific embodiment, the mass percentage of the rheology modifier in the adhesive layer is 0.5% to 3%, such as 0.5%, 1%, 1.5%, 2%, 2.5% or 3%, etc.; and / or, the mass percentage of the auxiliary agent in the adhesive layer is 0.1% to 2%, such as 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8% or 2%, etc. When the mass percentages of the rheology modifier and the auxiliary agent in the adhesive layer are respectively within the above ranges, the coating process of the adhesive layer is easier, and a diaphragm with fewer defects can be prepared, which is beneficial to the application of the diaphragm in the battery.
[0130] In a specific embodiment, the base film includes a polyolefin film and / or a non-woven fabric film, and the polyolefin film includes a polyethylene base film and / or a polypropylene base film. When the base film is made of the above materials, the diaphragm has high air permeability, which can ensure the rapid migration of ions between the positive and negative electrodes, thereby ensuring the electrochemical performance of the battery.
[0131] In a specific embodiment, the thermal shrinkage of the separator after baking at 130°C ± 5°C for 60min ± 5min is less than 5%. The thermal shrinkage of the separator within the above range can prevent the positive and negative electrodes of the battery from directly contacting each other, avoid short circuit of the battery, and thus improve the safety of the battery.
[0132] Specifically, the thermal shrinkage rate of the diaphragm of the embodiment of the present invention can be obtained by referring to the thermal shrinkage rate test in GB / T 36363-2018 "Polyolefin diaphragm for lithium ion battery":
[0133] Place the stainless steel plate and two quantitative filter papers in the middle of the oven, and control the temperature so that the stainless steel plate and filter paper reach (130±1)℃. Mark the longitudinal and transverse directions of the diaphragm, and use the length measuring instrument with corresponding resolution to measure the longitudinal and transverse lengths of the sample according to actual needs, and then place the diaphragm flat on one of the quantitative filter papers on the stainless steel plate in the middle of the blast thermostatic box. After completion, press it with another quantitative filter paper, close the thermostatic box door, start counting the time, and keep it at 130℃ for 1h.
[0134] After heating, take out the diaphragm, wait for the diaphragm to return to room temperature, and measure the longitudinal and transverse marking lengths again. Calculate the longitudinal and transverse shrinkage of the diaphragm according to the following formula, and take the average of the three test results as the thermal shrinkage of the diaphragm.
[0135] MD%=100%*(L z0 -L z ) / L z0 ,
[0136] TD%=100%*(L h0 -L h ) / L h0 ,
[0137] Where:
[0138] MD%: thermal shrinkage in the longitudinal direction of the diaphragm, %;
[0139] TD%: thermal shrinkage in the transverse direction of the diaphragm, %;
[0140] L z0 : The length of the diaphragm in the longitudinal direction before heating, in millimeters (mm);
[0141] L z : The length of the diaphragm in the longitudinal direction after heating, in millimeters (mm);
[0142] L h0 : The length of the diaphragm in the transverse direction before heating, in millimeters (mm);
[0143] Lh : The length of the diaphragm in the transverse direction after heating, in millimeters (mm).
[0144] In a specific embodiment, the permeability increment of the separator is not higher than 50s / 100cc. When the permeability of the separator is within the above range, the ions in the battery can quickly pass through the separator, realize rapid migration between the positive and negative electrodes, reduce the internal resistance of the battery, and thus improve the cycle performance of the battery.
[0145] Specifically, the air permeability of the diaphragm of the embodiment of the present invention can be reflected by testing the air permeability value increase through the following steps.
[0146] First, refer to GB / T 36363-2018 "Polyolefin separators for lithium-ion batteries" to test the air permeability time of the base film and the coated separator:
[0147] Cut three pieces of membrane from the film roll at 150mm intervals in the longitudinal direction. If the membrane width is ≥100mm, the sample size is 100mm×100mm. If the membrane width is <100mm, the sample size is 100mm×membrane width. Place the membrane in the test head of the permeability meter suitable for the test range to test the permeability time. Take the average value of the three test results as the permeability time of the membrane, in s / 100cc.
[0148] The membrane permeability value-added is the difference between the permeability time of the coated membrane and the permeability time of the base membrane, and the unit is s / 100cc.
[0149] The present invention provides a method for preparing the above-mentioned diaphragm, comprising the following steps: applying a slurry containing a first polymer binder to at least one surface of a base film to form an adhesive layer to obtain the diaphragm.
[0150] Specifically, the first polymer binder is mixed with water in a specified ratio to prepare a slurry containing the first polymer binder, and then the slurry is coated on at least one surface of the base film and dried to obtain an adhesive layer, that is, a diaphragm including a base film and an adhesive layer.
[0151] Furthermore, when the bonding layer further includes a second polymer binder, non-conductive particles, a rheology regulator and an additive, the bonding layer slurry can be obtained by mixing the first polymer binder, the second polymer binder, the non-conductive particles, the rheology regulator, the additive and water in a prescribed ratio.
[0152] The ratio of the mass of water to the total weight of solids in the bonding layer slurry of the embodiment of the present invention is (2.5-5):1, so that the solid content of the bonding layer slurry is 25%-45%.
[0153] The embodiment of the present invention does not limit the specific method of mixing the first polymer binder and water, for example, stirring, ultrasound, etc. can be selected according to actual needs.
[0154] The embodiment of the present invention does not limit the specific parameters of coating, which can be selected according to actual needs.
[0155] The embodiment of the present invention does not limit the specific parameters of drying, which can be selected according to actual needs.
[0156] The present invention can attach the adhesive layer to the surface of the base film through the preparation method to prepare a diaphragm with small thickness, low heat shrinkage and high air permeability, thereby ensuring high energy density, cycle performance and safety of the battery. In addition, the preparation method is simple in process, easy to operate and low in cost, which is conducive to the industrial production of diaphragms.
[0157] The invention provides a battery, which comprises a positive electrode sheet, a negative electrode sheet, and the above-mentioned diaphragm, wherein the diaphragm is located between the positive electrode sheet and the negative electrode sheet.
[0158] The battery of the embodiment of the present invention can be a lithium ion battery or a sodium ion battery. When the battery of the embodiment of the present invention is a lithium ion battery, the lithium ion battery of the embodiment of the present invention comprises a positive electrode sheet, the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer arranged on the surface of the positive electrode current collector, the positive electrode active material layer comprises a positive electrode active material, a conductive agent and a binder, wherein the positive electrode current collector is generally an aluminum foil. The positive electrode active material comprises a transition metal oxide of lithium, such as LiCoO2, LiMn2O4, LiMnO2, Li2MnO4, LiFePO4, LiNi x Co y Mn 1-x-y At least one of O2, wherein 0<x<1, 0<y<1.
[0159] The lithium-ion battery of an embodiment of the present invention includes a negative electrode sheet, which includes a negative electrode collector and a negative electrode active material layer arranged on the surface of the negative electrode collector, and the negative electrode active material layer includes a negative electrode active material, a conductive agent and a binder, wherein the negative electrode collector is generally a copper foil, and the negative electrode active material is selected from one or more of graphite, hard carbon, soft carbon, mesophase carbon microbeads, silicon-based negative electrode materials and lithium-containing metal composite oxide materials.
[0160] The conductive agent and the binder in the positive electrode active material layer and the negative electrode active material layer of the embodiment of the present invention can be selected from conventional materials in the art.
[0161] In a specific embodiment, the bonding force between the diaphragm and the positive electrode sheet is not less than 1.5 N / m; and / or, the bonding force between the diaphragm and the negative electrode sheet is not less than 0.5 N / m. When the bonding force between the diaphragm and the positive and negative electrode sheets is within the above ranges, the diaphragm can be bonded to the positive and negative electrode sheets, thereby fixing the battery structure, preventing the displacement of the positive and negative electrode sheets in the battery and causing the diaphragm to be pierced, and preventing the positive and negative electrode sheets from directly contacting each other, thereby improving the safety of the battery.
[0162] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0163] The present invention is further described below by specific examples and comparative examples. Unless otherwise specified, the reagents, materials and instruments used below are all conventional reagents, conventional materials and conventional instruments, which can be commercially available, and the reagents and materials involved can also be synthesized by conventional synthesis methods.
[0164] Example 1
[0165] The method for preparing the diaphragm of this embodiment comprises the following steps:
[0166] 1. The first polymer binder is obtained by polymerizing the monomer containing an unsaturated bond. The preparation process is as follows:
[0167] Step 1: Mix 20 parts of monomer with 0.5 parts of dilauroyl peroxide, stir and dissolve evenly to form a mixed monomer; the monomer used in this embodiment is a mixture of styrene, butyl acrylate, isooctyl acrylate, and divinyl benzene, and the mass ratio is 93:3:3:1;
[0168] Step 2: dissolving polyvinyl alcohol 1788 in 80 parts of deionized water to prepare a dispersant aqueous solution, with a dispersant concentration of 0.5 wt%;
[0169] Step 3: Pour the mixed solution of the first step into the dispersant aqueous solution of the second step, and homogenize into an oil-water dispersion at a speed of 5000 rpm using a high-speed homogenizer;
[0170] Step 4: After nitrogen is passed through for 30 minutes, the temperature is raised to polymerize. The polymerization temperature is 75° C. and the polymerization time is 6 hours. After the polymerization is completed, a first polymer binder aqueous dispersion with a solid content of 25% is obtained.
[0171] 2. The second polymer binder is prepared as follows:
[0172] Weigh 0.1 parts of sodium dodecyl sulfate and 350 parts of deionized water into a stirring container, add 85 parts of styrene and 65 parts of butadiene, control the stirring speed to 150±50rpm, stir and heat to 74±1°C, then add 0.8 parts of initiator, maintain stirring and react at 74±1°C for 6 hours, then raise the temperature to 79±1°C, continue the reaction for 3 hours, and obtain a second polymer binder emulsion with a solid content of 30%, an average particle size D502 of 0.8μm, a diameter distance of 0.9, and a glass transition temperature Tg2 of 12°C.
[0173] 3. Mix the first polymer binder, the second polymer binder, hydrated aluminum oxide, sodium carboxymethyl cellulose, an additive, and water to obtain an adhesive layer slurry, then apply the slurry on both sides of the polyethylene base film, and dry it to obtain a separator;
[0174] The thickness of the polyethylene-based film is 6 μm, and the thickness of the adhesive layer on one side of the polyethylene-based film is 1.5 μm;
[0175] In the adhesive layer, the average particle size D501 of the first polymer binder is 6 μm, the ratio of the average particle size of the first polymer binder to the thickness of the adhesive layer is 4:1, and the glass transition temperature Tg1 of the first polymer binder is 80° C.;
[0176] The mass percentage of the first polymer binder is 8%, the mass percentage of the second polymer binder is 6%, the mass percentage of hydrated alumina (average particle size D503 is 0.5μm, D103 is 0.2μm, D903 is 1.2μm) is 84.5%, the mass percentage of sodium carboxymethyl cellulose is 1%, and the mass percentage of the auxiliary agent is 0.5%.
[0177] Example 2
[0178] The preparation method of the diaphragm of this embodiment is substantially the same as that of Embodiment 1, except that the raw material composition for preparing the first polymer binder is a mixture of styrene, butyl acrylate, isooctyl acrylate, and divinylbenzene in a mass ratio of 95:1:2:2.
[0179] The monomer raw material composition for preparing the second polymer binder is a mixture of methyl methacrylate, butyl acrylate, isooctyl acrylate and divinylbenzene, with a mass ratio of 55:40:4:1.
[0180] The first polymer binder, the second polymer binder, the non-conductive particles and the separator are adjusted according to the values in Table 1.
[0181] Example 3
[0182] The preparation method of the diaphragm of this embodiment is substantially the same as that of Embodiment 1, except that the raw material composition for preparing the first polymer binder is a mixture of styrene, butyl acrylate, isooctyl acrylate, and divinylbenzene in a mass ratio of 79:10:10:1.
[0183] The monomer raw material composition for preparing the second polymer binder is a mixture of methyl methacrylate, butyl acrylate, isooctyl acrylate, and ethylene glycol diacrylate, with a mass ratio of 20:65:14:1.
[0184] The first polymer binder, the second polymer binder, the non-conductive particles and the separator are adjusted according to the values in Table 1.
[0185] Examples 4 to 8 and Comparative Examples 1 to 4
[0186] The preparation method of the diaphragm of this embodiment is substantially the same as that of Embodiment 1, except that the first polymer binder, the second polymer binder, the non-conductive particles and the diaphragm are adjusted according to the values in Table 1.
[0187] Table 1
[0188]
[0189]
[0190] Test Example 1
[0191] The thermal shrinkage rate, air permeability and bonding strength between the bonding layer and the base film of the diaphragm of the embodiment and the comparative example were tested:
[0192] Thermal shrinkage test
[0193] Refer to the heat shrinkage test in GB / T 36363-2018 "Polyolefin separator for lithium-ion battery". The specific method includes: placing a stainless steel plate and two quantitative filter papers in the middle of the oven, and controlling the temperature so that the stainless steel plate and the filter paper reach (130±1)℃. Mark the longitudinal and transverse directions of the diaphragm, and measure the longitudinal and transverse lengths of the sample using a length measuring instrument with corresponding resolution according to actual needs. Then, place the diaphragm flat on one of the quantitative filter papers on the stainless steel plate in the middle of the blast thermostat. After completion, press it with another quantitative filter paper, close the thermostat door, start counting the time, and keep it at 130℃ for 1h.
[0194] After heating, take out the diaphragm, wait for the diaphragm to return to room temperature, and measure the longitudinal and transverse marking lengths again. Calculate the longitudinal and transverse shrinkage of the diaphragm according to the following formula, and take the average of the three test results as the thermal shrinkage of the diaphragm.
[0195] MD%=100%*(L z0 -L z ) / L z0 ,
[0196] TD%=100%*(L h0 -L h ) / L h0 ,
[0197] Where:
[0198] MD%: thermal shrinkage in the longitudinal direction of the diaphragm, %;
[0199] TD%: thermal shrinkage in the transverse direction of the diaphragm, %;
[0200] L z0 : The length of the diaphragm in the longitudinal direction before heating, in millimeters (mm);
[0201] L z : The length of the diaphragm in the longitudinal direction after heating, in millimeters (mm);
[0202] L h0 : The length of the diaphragm in the transverse direction before heating, in millimeters (mm);
[0203] L h : The length of the diaphragm in the transverse direction after heating, in millimeters (mm).
[0204] Air permeability test
[0205] Refer to GB / T 36363-2018 "Polyolefin Separator for Lithium-ion Batteries" to test the air permeation time of the base film and the coated separator. The specific method includes: cut three pieces of separator 150mm apart in the longitudinal direction from the film roll. If the separator width is ≥100mm, the sample size is 100mm×100mm. If the separator width is <100mm, the sample size is 100mm×separator width. Place the separator in the test head of the permeator suitable for the test range to test the air permeation time. Take the average value of the three test results as the air permeation time of the separator, in s / 100cc.
[0206] The membrane permeability value-added is the difference between the permeability time of the coated membrane and the permeability time of the base membrane, and the unit is s / 100cc.
[0207] Bond strength test between adhesive layer and base film:
[0208] Test equipment:
[0209] Tensile testing machine: sensor range <200N; sensor resolution 0.01N, accuracy ±0.5%;
[0210] Support: Steel plate with a thickness of ≥1mm, smooth surface, length ≥150mm, width ≥25mm;
[0211] Test tape: single-sided tape with a viscosity of 0.4±0.05N / mm and a width of 19±0.5mm;
[0212] Ordinary double-sided tape: width>20mm,≤support width
[0213] Laminating wheel: 2.5kg smooth rubber roller
[0214] Specimen:
[0215] Three rectangular samples of 300 mm×50 mm were cut from the diaphragms prepared in the above-mentioned examples and comparative examples. If the width is between 20-50 mm, the sampling size is: 300 mm×diaphragm width.
[0216] Test steps:
[0217] Stick an ordinary double-sided tape with a width of more than 20mm flatly on one end of the support. The length of the ordinary double-sided tape is 120mm. Tear off the surface layer of the ordinary double-sided tape. Stick the adhesive layer of the diaphragm sample flatly on the ordinary double-sided tape, and roll it back and forth with a film pressing wheel to press it at least three times to expel the air between the ordinary double-sided tape and the sample. Stick the test tape flatly on the base film surface of the diaphragm sample, and roll it back and forth with a film pressing wheel to press it at least three times (the length of the test tape is 200-250mm). There should be no bubbles or folds at the bonding point between the adhesive layer surface and the ordinary double-sided tape, and between the base film surface and the test tape. Peel off the test tape and the coating outside the support body, and stop peeling the adhesive about 10mm after the ordinary double-sided tape is peeled off.
[0218] Adjust the test parameters of the tensile testing machine, test speed 50±5mm / min, peeling length 100±10mm, fixture spacing 120±10mm, test width 19mm, remove 25% (25mm) of the front end and the end. After adjusting the parameters, the lower chuck clamps the end of the support without double-sided tape, and the upper chuck clamps the test tape. When clamping the sample, pay attention to the sample being vertical. Start the test. After the test, read the average peel strength value of the interface as the 180° bonding strength value of the sample. Take the average value of the three samples as the 180° bonding strength of the sample, in N / m.
[0219] The test results are shown in Table 2.
[0220] Test Example 2
[0221] The separators of the embodiment and the comparative example are matched with the positive electrode sheet, the negative electrode sheet and the electrolyte to prepare a lithium ion battery. Specifically, the positive electrode active material LiNi 0.5 Co 0.2 Mn0.3 O2 (NCM523), conductive material CNT, conductive carbon black and binder (polyvinylidene fluoride) PVDF are dispersed in solvent NMP in a mass ratio of 94:2:2:2 to obtain a positive electrode active material layer slurry; the positive electrode active material layer slurry is evenly coated on the surface of the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained after drying, rolling, baking, slitting and spot welding of the pole ears.
[0222] The negative electrode active material artificial graphite, the conductive agent conductive carbon black, CNT, sodium carboxymethyl cellulose and the binder SBR are dispersed in deionized water in a mass ratio of 95:1.25:1.25:1.25:1.25, and stirred evenly to obtain a negative electrode active material layer slurry; the negative electrode active material layer slurry is evenly coated on the surface of the negative electrode current collector copper foil, and the negative electrode sheet is obtained after drying, rolling, baking, slitting and spot welding of the electrode ears.
[0223] An electrolyte is prepared in a glove box filled with argon gas with a purity of 99.999%, the moisture in the glove box is controlled at ≤0.1ppm, and the temperature is controlled at room temperature. Ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of EC:DMC:DEC=3:5:2, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1.2 mol / L. After mixing evenly, an electrolyte is obtained.
[0224] The prepared positive electrode sheet, negative electrode sheet and separator are stacked in order, the separator is placed between the positive electrode sheet and the negative electrode sheet, and after winding, the battery cell is placed in an aluminum-plastic film package, dried, and sealed by injecting electrolyte. After standing, forming, secondary sealing, capacity division and other processes, a lithium-ion battery is obtained.
[0225] The adhesion between the separator and the positive electrode sheet, and the adhesion between the separator and the negative electrode sheet were tested. The test results are shown in Table 2.
[0226] Table 2
[0227]
[0228] It can be seen from the test results in Table 2 that in the diaphragm provided by the present invention, the bonding strength between the adhesive layer and the base film is high, the bonding strength between the diaphragm and the electrode is high, and the thermal shrinkage rate and air permeability value added of the diaphragm itself are low, showing excellent air permeability and heat shrinkage resistance.
[0229] Specifically, by comparing Example 4 and Comparative Example 4, it can be seen that, in the case of low base film and adhesive layer thickness of the present invention, if the average particle size D503 of the non-conductive particles exceeds 0.8 μm, the thermal shrinkage rate of the separator will increase significantly.
[0230] It can be seen from the test results of Example 4 and Comparative Example 3 that if the diameter pitch of the second polymer binder exceeds 1, the bonding strength between the base film and the bonding layer will be significantly reduced, and the thermal shrinkage rate of the separator will be significantly increased.
[0231] By comparing the test results of Examples 1, 2, 4 and Comparative Examples 1 and 2, it can be seen that if the ratio of the average particle size D501 of the first polymer binder to the thickness of the adhesive layer is not within the range of 1.3-4, the bonding force between the diaphragm and the electrode will be significantly reduced.
[0232] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A diaphragm, characterized in that: It comprises a base film and an adhesive layer located on at least one side of the base film; the base film has a thickness of 3 to 6 μm, and the adhesive layer has a thickness of 0.5 to 1.5 μm; The adhesive layer includes a first polymer binder and non-conductive particles; the ratio of the average particle size D501 of the first polymer binder to the thickness of the adhesive layer is (1.3-4):1; the average particle size D503 of the non-conductive particles is 0.15-0.8 μm; the peel strength between the adhesive layer and the base film is above 10 N / m.
2. The diaphragm according to claim 1, characterized in that The average particle size D501 of the first polymer binder is 1 to 6 μm; And / or, the glass transition temperature Tg1 of the first polymer binder is 45-95°C.
3. The diaphragm according to claim 1, characterized in that The mass percentage of the first polymer binder in the adhesive layer is 3% to 15%; And / or, the first polymer binder is obtained by polymerizing a monomer containing an unsaturated bond, wherein: The monomer containing an unsaturated bond includes one or more of a vinyl monomer, a (meth)acrylate monomer, a maleate monomer, an itaconate monomer, a maleimide monomer, and a (meth)acrylamide monomer; And / or, the monomer containing an unsaturated bond includes one or more of a monomer having a carboxyl group, a monomer having a sulfonic acid group, a monomer having a phosphoric acid group, a monomer having a hydroxyl group, a monomer having an amino group, a monomer having an epoxy group, and a monomer having a cyano group.
4. The diaphragm according to claim 1, characterized in that The ratio of the average particle size D503 of the non-conductive particles to the average particle size D501 of the first polymer binder is 1:(2.3-20).
5. The diaphragm according to claim 4, characterized in that The average particle size D103 of the non-conductive particles is 0.05 to 0.6 μm, and the average particle size D903 of the non-conductive particles is 0.5 to 2 μm.
6. The diaphragm according to claim 1, characterized in that The mass percentage of the non-conductive particles in the bonding layer is 70% to 93.4%; And / or, the non-conductive particles include one or more of alumina, aluminum oxide, boehmite, silicon dioxide, titanium dioxide, zirconium dioxide, calcium oxide, magnesium oxide, magnesium hydroxide, calcium carbonate, barium titanate, barium sulfate, organic polymer microspheres, and organic polymer fibers.
7. The diaphragm according to any one of claims 1 to 6, characterized in that: The adhesive layer further includes a second polymer binder, and the average particle size D502 of the second polymer binder is 0.05-1 μm.
8. The diaphragm according to claim 7, characterized in that The second polymer binder has a diameter distance less than 1.
9. The diaphragm according to claim 6 or 7, characterized in that: The Tg2 of the second polymer binder is 20° C. or less.
10. The diaphragm according to claim 7, characterized in that The second polymer binder includes at least one of polyacrylate and styrene-butadiene latex; And / or, the mass percentage of the second polymer binder in the adhesive layer is 3% to 10%.
11. A diaphragm, characterized in that: It comprises a base film and an adhesive layer located on at least one side of the base film; the base film has a thickness of 3 to 6 μm, and the adhesive layer has a thickness of 0.5 to 1.5 μm; The bonding layer includes a first polymer binder, non-conductive particles and a second polymer binder; the ratio of the average particle size D501 of the first polymer binder to the thickness of the bonding layer is (1.3-4):1; the average particle size D503 of the non-conductive particles is 0.15-0.8 μm; the average particle size D502 of the second polymer binder is 0.05-1 μm, and the diameter distance of the second polymer binder is less than 1.
12. The diaphragm according to claim 11, characterized in that The average particle size D501 of the first polymer binder is 1 to 6 μm; And / or, the glass transition temperature Tg1 of the first polymer binder is 45-95°C.
13. The diaphragm according to claim 12, characterized in that The mass percentage of the first polymer binder in the adhesive layer is 3% to 15%; And / or, the first polymer binder is obtained by polymerizing a monomer containing an unsaturated bond, wherein: The monomer containing an unsaturated bond includes one or more of a vinyl monomer, a (meth)acrylate monomer, a maleate monomer, an itaconate monomer, a maleimide monomer, and a (meth)acrylamide monomer; And / or, the monomer containing an unsaturated bond includes one or more of a monomer having a carboxyl group, a monomer having a sulfonic acid group, a monomer having a phosphoric acid group, a monomer having a hydroxyl group, a monomer having an amino group, a monomer having an epoxy group, and a monomer having a cyano group.
14. The diaphragm according to any one of claims 11 to 13, characterized in that: The ratio of the average particle size D503 of the non-conductive particles to the average particle size D501 of the first polymer binder is 1:(2.3-20).
15. The diaphragm according to claim 14, characterized in that The average particle size D103 of the non-conductive particles is 0.05 to 0.6 μm, and the average particle size D903 of the non-conductive particles is 0.5 to 2 μm; And / or, the mass percentage of the non-conductive particles in the adhesive layer is 70% to 93.4%; And / or, the non-conductive particles include one or more of alumina, aluminum oxide, boehmite, silicon dioxide, titanium dioxide, zirconium dioxide, calcium oxide, magnesium oxide, magnesium hydroxide, calcium carbonate, barium titanate, barium sulfate, organic polymer microspheres, and organic polymer fibers.
16. The diaphragm according to claim 11, characterized in that The Tg2 of the second polymer binder is below 20°C; And / or, the second polymer binder includes at least one of polyacrylates and styrene-butadiene latex; And / or, the mass percentage of the second polymer binder in the adhesive layer is 3% to 10%.
17. A battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, and a separator according to any one of claims 1 to 10 or a separator according to any one of claims 11 to 16, wherein the separator is located between the positive electrode sheet and the negative electrode sheet.
Citation Information
Patent Citations
High-temperature-resistant heat-shrinkable lithium battery diaphragm and preparation method thereof
CN110993866A
Water-based paint for lithium ion battery composite diaphragm, lithium ion battery composite diaphragm and lithium ion battery
CN112940650A
Ceramic composite diaphragm and lithium ion battery
CN114374052A
Narrow distribution diaphragm binder and preparation method thereof, lithium ion battery diaphragm and lithium ion battery
CN117060010A
Cited By
Composite diaphragm, preparation method thereof and lithium ion battery
CN121367023A
Separator and battery
WO2026066468A1